Annular Gas and Drillstring's Transverse Amplitude. Issue 1 (January 2021) - Wang, Chaofei; Shi, Jiangang; Xi, Chuanming; Chu, Hengzhi; Zhu, Zhongxi
Abstract: In drilling construction, drill string's transverse vibration greatly improves the drill risk and complexity. Drill string is in buckling will lead it in transverse vibration, at the same time, when gas invasion appears into annular, drill string vibration will be intensified, which will create severe fatigue breakdown to drill string and improve the drill complexity. This paper has established a two-dimensional fluid-structure coupling model by CFD software to research the effect annular gas on drill string's transverse vibration and explore the function relation between gas volume and drill string transverse amplitude. The modelling is established in static vertical interval, 1m drill string, and set the gas column length range from 88.9mm to 226.7mm to explore the law of the annular air in different well depth and transverse vibration of drill string. It can be used to predict the maximum amplitude which created by gas flowing out, so as to judge whether drill string will touch the well wall and vibrate.